2018
DOI: 10.1074/jbc.ra118.004722
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase activity of small C-terminal domain phosphatase 1 (SCP1) controls the stability of the key neuronal regulator RE1-silencing transcription factor (REST)

Abstract: The RE1-silencing transcription factor (REST) is the major scaffold protein for assembly of neuronal gene silencing complexes that suppress gene transcription through regulating the surrounding chromatin structure. REST represses neuronal gene expression in stem cells and non-neuronal cells, but it is minimally expressed in neuronal cells to ensure proper neuronal development. Dysregulation of REST function has been implicated in several cancers and neurological diseases. Modulating REST gene silencing is chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Among these studies, Burkholder et al showed that miR‐124a suppressed the expression of small C‐terminal domain phosphatase 1 ( SCP1 ) by targeting its 3′‐UTR region. Interestingly, SCP1 , on the other hand, dephosphorylates RE1‐silencing transcription factor ( REST ) and protects it from degradation . REST , in turn, is a neuronal repressor that negatively regulates miR‐124a expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, Burkholder et al showed that miR‐124a suppressed the expression of small C‐terminal domain phosphatase 1 ( SCP1 ) by targeting its 3′‐UTR region. Interestingly, SCP1 , on the other hand, dephosphorylates RE1‐silencing transcription factor ( REST ) and protects it from degradation . REST , in turn, is a neuronal repressor that negatively regulates miR‐124a expression.…”
Section: Discussionmentioning
confidence: 99%
“…Another cooperative factor, active during neuronal differentiation, is the C-terminal domain phosphatase 1 (SCP1), an enzyme that regulates the phosphorylation of REST. SCP1 protects REST from degradation, making possible the typical changes of its level at specific sites of differentiation (4). Plant Homeo Domain Finger protein 8 (PHF8), a chromatin regulator in many cell types, operates as a transcriptional activator.…”
Section: Cooperative Interactionsmentioning
confidence: 99%
“…High REST is present also in neurons and neural cells, limited, however, to their stem and early progenitor states, where regulation is peculiar [3][4][5]. For these reasons, the early cells share properties with non-neural cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative strategy may therefore be to modulate REST activity indirectly by targeting CTDSP1, the phosphatase that protects it from degradation. While CTDSP1 knockdown has been shown to promote neurotrophic factors expression in HEK-293 cells [19], it is not known whether it effectively promotes neurotrophic factor expression in neurons or in support cells. Here, we investigate whether the REST pathway is active in MPCs.…”
Section: Introductionmentioning
confidence: 99%